ANALISIS TINGKAT KERUNTUHAN ELEMEN KOLOM BETON BERTULANG AKIBAT PEMBEBANAN STATIK MENGGUNAKAN SOFTWARE ELEMEN HINGGA - Toni, Nopember; Suryanita, Reni; ', Ismeddiyanto (Proceedings ACES (Annual Civil Engineering Seminar), 2015)
Column failure is one of failure conditions in building where column cannot receive any moreload from beam or another element. Therefore in designing column required more accuratecalculation which need more time with manual calculation. The solution in designing columnwith accurate calculation and faster is using finite element software. Finite element softwarecan calculate column strain with high precision result. In this paper, column failure determinedwith the result of column strain. Column used in this paper using variation in: column sectiondimension, concrete ultimate capacity, longitudinal reinforcement, and steel ultimate capacity.With all variation, total data used in this research is 10962 data. In this paper, column damagelevel noted as 0 if DL less than 1 and that mean column do not reach failure level, whilecolumn damage level noted as 1 if DL more equal than 1 and that mean column reach failurelevel. Result from finite element software analysis shows that column strain increase with theincrease of column parameter such as column section dimension. And column strain resultsfrom finite element software have similar result with analysis using flexure method. Thisresults shows finite element software can be used in column failure analysis.Kata kunci: Damage level, finite element, reinforced concrete column.